Skrining Penyakit Menular dan Tidak Menular pada Ibu Hamil di Wilayah Kuta Selatan, Bali: Screening for Communicable and Non-Communicable Diseases among Pregnant Women in South Kuta, Bali - Armini, Luh Nik; Made Adiantini; Prayudi, Made Aristia; Suputra, Putu Adi (Indonesian Journal of Midwifery (IJM), 2025)
The World Health Organization (WHO) recommends that every pregnant woman have a positive and fulfilling experience throughout pregnancy, childbirth, and the postpartum period. Comprehensive screening as part of integrated antenatal care (ANC) is an essential effort for early detection and prevention of complications during these stages. This study aimed to determine the proportion of integrated ANC screening results, including communicable diseases (HIV, syphilis, and hepatitis B) and non-communicable conditions (anemia, chronic energy deficiency [CED], preeclampsia, and gestational diabetes) among pregnant women in the catchment area of South Kuta Health Center, Bali. This study employed a cross-sectional design using secondary data collected between June and September 2024. A total sampling technique was applied to all records that met the inclusion criteria, resulting in 684 cases for analysis. Data were analyzed descriptively using frequency and percentage distributions. The highest proportion was anemia (36.4%), followed by CED (10.2%), underweight (8.8%), obesity (5.6%), gestational diabetes (0.4%), preeclampsia (0.9%), hepatitis B (1.3%), syphilis (0.7%), and HIV (0.4%). Most maternal health problems were related to nutritional factors, particularly anemia and CED. Although the proportions of preeclampsia, gestational diabetes, and communicable diseases were relatively low, early detection through regular and timely ANC screening remains crucial for preventing maternal and perinatal complications. Strengthening maternal nutrition programs through improved adherence to iron–folate supplementation, close monitoring of dietary intake, and continuous nutrition education is recommended to minimize the risk of anemia and CED among pregnant women.   Abstrak WHO merekomendasikan setiap ibu hamil memiliki pengalaman yang menyenangkan selama proses kehamilan, persalinan, dan nifas. Pelaksanaan skrining secara komprehensif dalam ANC terpadu merupakan upaya deteksi dini yang penting dalam mencegah komplikasi selama masa kehamilan, persalinan, dan nifas. Tujuan dari penelitian ini untuk mengetahui proporsi hasil skrining ANC terpadu meliputi penyakit menular (HIV, sifilis, dan hepatitis B) dan tidak menular (anemia, KEK, preeklamsia, diabetes gestasional) pada ibu hamil di wilayah kerja Puskesmas Kuta Selatan, Bali. Desain penelitian menggunakan studi pontong lintang (cross-sectional) menggunakan data sekunder. Data sekunder yang diambil selama periode penelitian Juni-September 2024. Teknik sampling menggunakan total sampling yang memenuhi kriteria inklusi yaitu memiliki data yang lengkap (n=684). Data dianalisis secara deskriptif menggunakan distribusi frekuensi dan persentase. Proporsi hasil skrining tertinggi adalah anemia (36,4%), diikuti KEK (10,2%), underweight (8,8%), obesitas (5,6%), diabetes gestasional (0,4%), preeklamsia (0,9%,     hepatitis B (1,3%), sifilis (0,7%), dan HIV (0,4%). Sebagian besar masalah kesehatan ibu hamil yang ditemukan di Puskesmas Kuta Selatan karena masalah gizi (anemia dan KEK). Walaupun proporsi preeklampsia, diabetes gestasional, dan penyakit menular relatif lebih rendah, deteksi dini melalui skrining rutin dan tepat waktu saat melakukan ANC tetap diperlukan untuk mencegah komplikasi maternal dan perinatal. Penguatan program gizi perlu dilakukan melalui peningkatan kepatuhan konsumsi tablet tambah darah, pemantauan asupan nutrisi, serta edukasi gizi yang berkelanjutan agar risiko anemia dan KEK dapat diminimalkan.